Acerca del dinero electrónico o digital - Blossiers Mazzini, Juan José (2013)
The present article exposes the scope and dimensión of the new electronic money, analyzing its opera!ion, emtssion procedure and security guarantees for the consumen explaining in detail the evotutionary scenery of this system in the future. In this way, the author fundaments the importance and repercuss ion of the electronic money in the Economy, the Finances as well as the Commerce, finahzing with an interesting analysis of the impact of this new electronic payment ahove the law and its international regulation. In that sense, the text refers the henefits of the use of the electronic money hoping soon to he of general application.